Energy Potential of the Bratislava Neogene - Slavkov Juraj; Tomajková Dana; Brček Martin; Miča Lumír (Civil and Environmental Engineering)
The thermal conductivity of materials is characteristic extensively applied across various contemporary domains, ranging from civil engineering to agriculture. The capacity of a material to conduct heat underscores its significance primarily within civil engineering, particularly in energy-related applications. Notably, in the design of energy geostructures, the thermal conductivity of the soil assumes paramount importance. The principle of energy geostructures is to extract geothermal energy, where the base soil works as a heat source. As the thermal conductivity of the ground increases, the amount of extracted energy increases. It can be concluded that the exact determination of the thermal conductivity of the ground has a significant impact on the design of energy geostructures. This article is dedicated to the first detailed measurements of the thermal conductivity of the Bratislava Neogene in five selected localities on samples from depths of 7.1 m to 14.4 m.